The socio-environmental problematic in Conservation Units:: conflicts and discourses for the use and access to natural resources - Giraldi Costa, Ana Clara; Murata, Afonso Takao (Sustainability in Debate, 2015)
Historically, the establishment of protected areas such as the Conservation Units has given rise to complex situations of socio-environmental conflicts, either because of the relocation of populations living in such areas, or as a consequence of the restriction of the access and customary use of natural resources contained therein. In this context, this literature-review article focuses on socio-environmental conflicts, especially those that take place around areas of integral protection, elucidating the main streams of environmentalism that approach the topic. From the theoretical insights into the subject, it was observed that the field is permeated by intense debate between social-environmentalists and conservationists, who argue mainly about the legal right of populations to remain in and use resources from such areas, as opposed to the need of preserving an ecosystem from any human presence.